Characterization, management, and risk factors of hyperglycemia during PI3K or AKT inhibitor treatment. (25th February 2022) - Liu, Dazhi; Weintraub, Michael A.; Garcia, Christine; Goncalves, Marcus D.; Sisk, Ann Elizabeth; Casas, Alissa; Harding, James J.; Harnicar, Stephen; Drilon, Alexander; Jhaveri, Komal; Flory, James H.
Abstract: Purpose: The phosphoinositide 3‐kinase (PI3K)/protein kinase B (AKT) pathway controls insulin sensitivity and glucose metabolism. Hyperglycemia is one of the most common on‐target adverse effects (AEs) of PI3K/AKT inhibitors. As several PI3K and AKT inhibitors are approved by the United States Food and Drug Administration or are being studied in clinical trials, characterizing this AE and developing a management strategy is essential. Methods: Patients with hematologic or solid malignancies treated at Memorial Sloan Kettering Cancer Center with a PI3K or AKT inhibitor were included in this retrospective analysis. A search for patients experiencing hyperglycemia was performed. The frequency, management interventions and outcomes were characterized. Results: Four hundred and ninety‐one patients with 10 unique cancer types who received a PI3K or AKT inhibitor were included. Twelve percent of patients required a dose interruption, 6% of patients required a dose reduction and 2% of patients were hospitalized to manage hyperglycemia. No events occurred among patients receiving β ‐, γ ‐, or δ ‐ specific PI3K inhibitor. There was one case where the PI3K or AKT inhibitor was permanently discontinued due to hyperglycemia. Metformin was the most commonly used antidiabetic medication, followed by insulin, sodium‐glucose transport protein 2 (SGLT2) inhibitors, and sulfonylurea. SGLT2 inhibitors were associated with the greatest reductions in blood sugar, followed by metformin. At least one case of euglycemic diabetic ketoacidosis (DKA) occurred in a patient on PI3K inhibitor and SGLT2 inhibitor. Body mass index ≥ 25 and HbA1c  ≥ 5.7 are were independently significant predictors of developing hyperglycemia. Conclusion: Hyperglycemia is one of the major on‐target side effects of PI3K and AKT inhibitors. It is manageable with antidiabetic medications, treatment interruption and/or dose modification. We summarize pharmacological interventions that may be considered for PI3K/AKT inhibitor induced hyperglycemia. SGLT2‐inhibitor may be a particularly effective second‐line option after metformin but there is a low risk of euglycemic DKA, which can be deadly. To our knowledge, our report is the largest study of hyperglycemia in patients receiving PI3K/AKT inhibitors. Abstract : Phosphoinositide 3‐kinase (PI3K)/protein kinase B (AKT) inhibitor induced hyperglycemia is particularly likely to happen in patients with baseline diabetes, pre‐diabetes, or elevated body mass index. It is manageable with dose interruption, dose modification and/or pharmacologic management; and that sodium‐glucose transport protein 2 inhibitors are a promising second‐line option after metformin.